Tutti Fratelli? Perspectives and Challenges for International Humanitarian Law - Keith, Kenneth J (Victoria University of Wellington Law Review, 2010)
This article is based on addresses given in The Hague, Wellington and Auckland in 2009 to mark the 150th anniversary of the beginnings of the International Red Cross and Red Crescent Movement. Out of a dreadful day of war, the Battle of Solferino, was born a great humanitarian institution which later became the International Committee of the Red Cross. The author discusses seven matters from the early years of the organisation: first was the importance of simple humanity; second was the principle of non-discrimination; third was a positive obligation to collect and care for the wounded and sick; fourth was about the rights and responsibilities of the individuals involved in warfare; fifth was the importance of getting peace agreements before hostilities began; sixth was establishing of national societies for the relief for the wounded before the same; and finally, the law was inherently humanitarian in nature. The author then discusses the implementation of international humanitarian law, arguing for two main methods: education and training programmes, and compliance through negotiation with governments. The author stresses the importance of adhering to laws during times of warfare by emphasising the values on which the law is based.